Gaps and challenges of the European network of protected sites in the marine realm. (10th August 2017) - Mazaris, Antonios D; Almpanidou, Vasiliki; Giakoumi, Sylvaine; Katsanevakis, Stelios
Abstract: The Natura 2000 network forms the cornerstone of the biodiversity conservation strategy of the European Union and is the largest coordinated network of protected areas (PAs) in the world. Here, we demonstrated that the network fails to adequately cover the marine environment and meet the conservation target of 10% set by the Convention on Biological Diversity. The relative percentage of marine surface cover varies significantly among member states. Interestingly, the relative cover of protected seascape was significantly lower for member states with larger exclusive economic zones. Our analyses demonstrated that the vast majority (93%) of the Natura 2000 sites that cover marine waters include both a terrestrial and a marine component. As a result, the majority of the protected surfaces is adjacent to the coastline, and decreases offshore; only 20% of Natura marine PAs is at depths >200 m. The lack of systematic planning processes is further reflected by the great variability in the distances among protected sites and the limited number of shared Natura sites among member states. Moreover, <40% of the marine sites have management plans, indicating the absence of active, or limited management in most sites. This work highlights the gaps in coverage and spatial design of the European conservation network in the marine environment, and raises questions on the unevenly treatment of marine vs. terrestrial areas.